Changing of Health Behavior for Blood Sugar Level Control in Diabetes Mellitus Patients: Roi-et Hospital 2010 - Pienpasertkul, Sakda (Journal of Health Science of Thailand, 2017)
The objective of this descriptive study was to test effectiveness of optimal health behavior change model of diabetes mellitus patient in Roi-et hospital, 2010. Study sample was diabetes mellitus outpatients at Roi-et hospital with blood sugar over 180 mg/dl for 3 consecutive months. Health behavior change model in this was activity knowledge for sample group and guideline practice for blood sugar level control. The activity consisted of general education on diabetes mellitus, knowledge for advanced diabetes mellitus patient on food control, exercise and used drug for blood sugar level control. Data were collected by a questionnaire constructed by the researcher. Comparisons, of effectiveness of health behavior change of diabetes patient as measured by blood sugar level using at pre and post testing after 3 month were made. The data from this study were analyzed and presented using descriptive statistics as percentage, mean, standard deviations, and chi-square test for correlation. The analysis finding showed that post activity testing of health behavior of food control, exercise, and medication of diabetes patients better than pre-activity (p<0.05) and blood sugar level in sampling group was lower than pre-testing. (p< 0.05). It is concluded that this model should be applicable in similar social and cultural setting with good financial and supporting team.